Attitude, Knowledge and Practice of Contraceptive Methods in Rural Areas - Noreen Rasul, Sidra Afzal, Sara Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Promotion of family planning has been shown to reduce maternal and neonatal mortality and promotes women empowerment. Contraception is regarded as an important preventive measure against unintended pregnancies. Although contraceptive methods are freely available in Family Planning centers, the utilization is low. Aims And Objectives: To assess the attitude, knowledge and practice of contraceptive methods in rural areas Material and Method: The study was carried in Pak Rd Crescent Medical and Dental College, Dinanath. Duration was 6 months from 1 July 2021 till 31 December 2021. It was a descriptive study. Sample size was 1200. Postoperative patients including caesarean section and spontaneous vaginal delivery and patients coming in outpatient department including antenatal and patients with gynecological problems were included. The women were interviewed regarding knowledge of contraceptive methods and choice to decide these methods. Most of them had knowledge but less number of women agreed to decide family planning method. Results: Usually women who gave interview were between age 31 to 40 years 37.6% and21 to 30 years 33.1%. Maximum parity 2 -4 were 47.1% and P 5 and above were 44.7%. 69.3% of them were illiterate. 86.4% women had knowledge of IUCD, 91.8% regarding COCP and 91.1% about injectable contraceptives.95.6% knew about male condoms. For the practice of contraceptive methods, maximum demand was of male condoms 13.8%, COCP 9.5%, IUCD 4% and injectables 4.6%. The reasons for not practicing family methods were husband and family pressure 30.1%, different myths about contraception 27.2%, family not complete 17.6%, cultural reasons 14.6%, lack of knowledge 8.8% and need for male gender 4.5% Conclusion: Although most of the ladies had knowledge of contraceptive methods but they were reluctant to practice them. Motivation of husband and mother in law is important factor to achieve positive attitude towards contraception. Counselling against myths and false belief is essential.